2011
DOI: 10.1016/j.freeradbiomed.2011.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrosyliron complexes are the most abundant nitric oxide-derived cellular adduct: biological parameters of assembly and disappearance

Abstract: It is well established that nitric oxide (•NO) reacts with cellular iron and thiols to form dinitrosyliron complexes (DNIC). Little is known, however, regarding their formation and biological fate. Our quantitative measurements reveal that cellular concentrations of DNIC are proportionally the largest of all •NO-derived adducts (900 pmol/mg protein (45–90 μM)). Using murine macrophages (RAW 264.7), we measured the amounts, and kinetics of, DNIC assembly and disappearance from endogenous and exogenous sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
150
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(167 citation statements)
references
References 31 publications
13
150
2
2
Order By: Relevance
“…Similar to our result shown in Fig. 2, higher DNIC production from bolus ⅐ NO addition in hypoxic cells has been reported previously, and this increase was attributed to the higher ⅐ NO level (2). To test this possibility, we used an ⅐ NO electrode to follow the real-time ⅐ NO level after addition to the cell suspension pretreated with 1 h of anoxia or normoxia.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Similar to our result shown in Fig. 2, higher DNIC production from bolus ⅐ NO addition in hypoxic cells has been reported previously, and this increase was attributed to the higher ⅐ NO level (2). To test this possibility, we used an ⅐ NO electrode to follow the real-time ⅐ NO level after addition to the cell suspension pretreated with 1 h of anoxia or normoxia.…”
Section: Resultssupporting
confidence: 85%
“…3A, the rapid ⅐ NO consumption indicates that significant anoxia has not been achieved under this condition. As explained under "Discussion," this could explain the overestimation of DNIC formation from the bolus ⅐ NO addition under "normoxia" (2).…”
Section: Preparation Of Standards For the Quantitation Of Epr Spectra-mentioning
confidence: 98%
See 1 more Smart Citation
“…These salts and certain Roussin's red esters (RREs) have been studied as potential sources of therapeutic NO either thermally [22] or photochemically activated [23][24][25][26][27][28][29]. In addition, both mononitrosyl iron complexes (MNICs) and dinitrosyl iron complexes (DNICs) are drawing increasing attention with regard to their potential roles in mammalian physiology [30][31][32][33][34]. The structures drawn in Fig.…”
Section: Metal-nitrosyl Bondingmentioning
confidence: 99%
“…Despite reports that dinitrosyl-iron complexes are the most abundant nitric oxide-derived cellular adducts [34], quantitative investigations of DNIC formation are quite limited. Vanin and coworkers [107] studied the reaction between Fe 2+ , nitrosothiol (RSNO), and thiol (RSH ¼ cysteine or glutathione) and demonstrated that first a mononitrosyl iron complex Fe(NO)(RS) n is formed followed by formation of the DNIC [Fe(NO) 2 …”
mentioning
confidence: 99%